2022
DOI: 10.3389/fphys.2022.834812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aquatic Exercise in Post-exercise Hypotension: A Systematic Review and Meta-Analysis

Abstract: BackgroundPost-exercise hypotension (PEH) can be an important non-pharmacological strategy in the treatment of arterial hypertension. Both aerobic and resistance exercises produce PEH, but it is not clear if the exercise environment can lead to a higher PEH.ObjectiveThis meta-analysis investigated whether a session of aquatic exercise (AE) induces PEH in comparison with control conditions such as land exercise (LE) or rest in hypertensive subjects.MethodsThe present systematic review and meta-analysis was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…A recent meta-analysis 17 , which was conducted with hypertensive individuals, compared the hypotensive effects of an aquatic exercise session with a control session and found similar results. The study indicated that exercise in the aquatic environment reduced SBP by -6,0 mmHg and DBP by -1,9 mmHg but without signi cant effects over 24 hours 17 . Acute BP responses are of great clinical relevance as they provide essential data on chronic BP adaptations in addition to reducing acute cardiovascular risk 8 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent meta-analysis 17 , which was conducted with hypertensive individuals, compared the hypotensive effects of an aquatic exercise session with a control session and found similar results. The study indicated that exercise in the aquatic environment reduced SBP by -6,0 mmHg and DBP by -1,9 mmHg but without signi cant effects over 24 hours 17 . Acute BP responses are of great clinical relevance as they provide essential data on chronic BP adaptations in addition to reducing acute cardiovascular risk 8 .…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis evaluated BP responses in hypertensive individuals (> 18 years) after aquatic exercise compared to a control condition (land-based exercise or rest) and found no differences in 24-hour responses between the sessions. However, SBP and DBP decreased during the night period (8,6 mmHg and 3,7 mmHg, respectively) compared to land-based exercise, and DBP showed a signi cant reduction (1.7 mmHg) after aquatic exercise versus rest 17 . It is known that methodological differences can in uence these results, such as the studied population, the exercise session protocol, and the comparison between land and water exercise sessions.…”
Section: Introductionmentioning
confidence: 85%
“…Visto o grande impacto causado pela HAS, uma das terapias não farmacológicas recomendadas é o treinamento de 90-150 min de atividade aeróbica com intensidade moderada a vigorosa por semana, onde observa-se redução de cerca de -3/-3,5 mmHg na PA, pois a atividade gera adaptações cardiovasculares e respiratórias a fim de suprir as necessidades musculares, após as primeiras alterações ocorre a hipotensão-pós-exercício (HPE), considerado um fator positivo no tratamento da HAS (GOMES et al, 2019;TRINDADE et al, 2022).…”
Section: Resultsunclassified